Analysis of Borrowings and Repayment of Fisherfolk in Selected Fishing Villages of Tamilnadu - R., Senthilathiban; M., Raja Kumar; R.K., Ram Kumar (Fishery Technology, 2025)
A study on the borrowings and repayment of fisherfolk in two fishing villages in Kanyakumari district of Tamilnadu was taken up. The purpose-wise and source-wise borrowings and the source-wise repayment of the fishermen respondents were analysed. The factors affecting the borrowings and indebtedness of fishermen respondents are presented.